Drilling and completion technologies of coalbed methane exploitation: an overview - Tianshou Ma; Jinhua Liu; Jianhong Fu; Bisheng Wu (International Journal of Coal Science & Technology, 2022)
Abstract Coalbed methane (CBM) drilling and completion technologies (DCTs) are significant basis for achieving efficient CBM exploration and exploitation. Characteristics of CBM reservoirs vary in different regions around the world, thereby, it is crucial to develop, select and apply the optimum DCTs for each different CBM reservoir. This paper firstly reviews the development history of CBM DCTs throughout worldwide and clarifies its overall development tendency. Secondly, different well types and its characteristics of CBM exploitation are summarized, and main application scopes of these well types are also discussed. Then, the key technologies of CBM drilling (directional drilling tools, measurement while drilling, geo-steering drilling, magnetic guidance drilling, underbalanced drilling and drilling fluids), and the key technologies of CBM completion (open-hole, cavity and under-ream completion, cased-hole completion, screen pipe completion and horizontal well completion) are summarized and analyzed, it is found that safe, economic and efficient development of CBM is inseparable from the support of advanced technologies. Finally, based on the current status of CBM development, the achievements, existing challenges and future prospects are summarized and discussed from the perspective of CBM DCTs.